Konut kooperatiflerinde pazarlama sorunları ve İstanbul ilinde bir uygulama - Kaplan, Mehmet Kemal (My University, 2008)
19. Yüzyılda Sanayi Devrimi ile tüm dünya ülkelerinde kentleşme hızı artmış, bunun sonucu olarak konut sıkıntıları baş göstermeye başlamıştır. Ülkemizde de 1950’li yıllardan itibaren ekonomik, toplumsal ve politik değişim sürecine girilmiş, bu değişimlerin türevi olarak kırdan kente olan göçler nedeniyle konut sorunu ortaya çıkmıştır. Büyük kentlerdeki büyüme hızına devletin çözüm politikaları yetersiz kalmış ve büyük şehirlerde gecekondu tabir edilen sorunlu mahalleler türemeye başlamıştır. Konut açığının her geçen yıl katlanarak artması sorunu, yeni çözümler aranmasını gerektirmiş ve karşımıza toplu konut yapımı ve kooperatifçilik çıkmıştır. Bu çalışma ile konut kooperatiflerinin ülkemizdeki gelişim seyri ile genel ve pazarlama sorunları anlatılmaya çalışılmış; İstanbul ilinde faaliyet gösteren konut kooperatif yönetim kurulu üyeleriyle görüşmeler yapılarak, konut kooperatiflerinin sorunları ve çözüm önerileri hakkındaki fikirleri alınmıştır.

MARKETING PROBLEMS FOR RESIDENTIAL COOPERATIVES AND AN IMPLEMENTATION IN ISTANBUL Housing became a major issue after the Industrial revolution of the 19th century brought with it an increase in urbanization worldwide. Since the 1950’s, Turkey has undergone a series of economical, social and political changes. These changes have led to an increase in migration from rural to urban areas, which has raised a concern over the supply of residences in these areas. The Turkish government’s solution for increasing population in urban areas by providing housing was not enough and as an outcome people began to build Gecekondus, which are small houses built in a very short amount of time without the necessary permits and infrastructure. The increasing difference between the population and the number of residences every year compelled the government to seek different solutions. Ultimately, corporate housing residences were built to solve this issue. This thesis seeks to explain the development as well as the general and marketing difficulties of these cooperatives, and provides insights of various cooperative board members working in Istanbul on the problems and solutions related to corporate housing.
Keywords: Konut Kooperatifleri; Pazarlama